Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1038/ctg.2015.54
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Bowel Preparation on Microbiota-Related Metrics Differ in Health and in Inflammatory Bowel Disease and for the Mucosal and Luminal Microbiota Compartments

Abstract: OBJECTIVES:Bowel preparations (BPs) taken before colonoscopy may introduce a confounding effect on the results of gastrointestinal microbiota studies. This study aimed to determine the effect of bowel preparation on the mucosa-associated and luminal colonic microbiota in healthy subjects (HC) and inflammatory bowel disease (IBD) patients.METHODS:Biopsy samples (n=36) and fecal samples (n=30) were collected from 10 HC and 8 IBD subjects pre- and post-BP. 16S rRNA gene was pyrosequenced using 454 Titanium protoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
81
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 55 publications
(61 reference statements)
0
81
0
Order By: Relevance
“…The study demonstrated that bowel prep affected the composition and diversity of the microbiota in the short term differently between sample types with differences also noted between controls and IBD patients. Biopsies from healthy subjects showed greater changes due to bowel prep compared to IBD patients [40]. …”
Section: Discussionmentioning
confidence: 99%
“…The study demonstrated that bowel prep affected the composition and diversity of the microbiota in the short term differently between sample types with differences also noted between controls and IBD patients. Biopsies from healthy subjects showed greater changes due to bowel prep compared to IBD patients [40]. …”
Section: Discussionmentioning
confidence: 99%
“…Only longitudinal studies with sampling at multiple time points can aid in making this distinction. Diet, likely to be altered in many disease states, can significantly modify the microbiome (in both the long and short terms) and has not been accounted for in many of studies. For obvious reasons of convenience, most human studies have been based on the analysis of faecal samples, an approach that disregards variations in bacterial populations along the length of the gastrointestinal tract and may fail to represent those bacterial populations that reside close to or adherent to the mucosa. Though more challenging in terms of access, studies of the juxta‐mucosal microbiome in the colon have revealed significant difference in health and disease from those studies where microbiome analyses were based on stool samples (Parthasarathy et al, ; Ringel et al, ; Shobar et al, ). Even more logistically challenging are studies of the small intestinal microbiome; here also, new data are appearing (Saffouri et al, ).…”
Section: What Do We Know?mentioning
confidence: 99%
“…Though more challenging in terms of access, studies of the juxtamucosal microbiome in the colon have revealed significant difference in health and disease from those studies where microbiome analyses were based on stool samples (Parthasarathy et al, 2016;Ringel et al, 2015;Shobar et al, 2016). Even more logistically challenging are studies of the small intestinal microbiome; here also, new data are appearing (Saffouri et al, 2019).…”
Section: What Do We Know?mentioning
confidence: 99%
“…Drago et al 50 compared the microbiota composition immediately and 1 month after MBP; contrary to most other studies, they found that MBP has long-lasting effects on the gut microbiota composition and homeostasis, particularly in terms of a decrease in the abundance of Lactobacillaceae , a population of protective bacteria (figure 3). Shobar et al 51 conducted one of the most thorough studies, which simultaneously analysed the composition of the microbiota at the levels of the mucosal and luminal compartments, differentiating between healthy subjects and patients with IBD and using a high-resolution technique.…”
Section: The Impact Of Preoperative Mechanical Bowel Preparation Withmentioning
confidence: 99%
“…In addition, the initial composition of the gut microbiota might already be dysbiotic and therefore not ‘normal’ because of the specific disease to be treated. However, there is no doubt, for example, that the microbiota in patients with IBD suffers from significant changes in its bacterial composition 51. Even though data are scarce for the moment, we can presume that other diseases that will finally point towards a colorectal surgery such as repeated diverticulitis or colorectal cancer are also characterised by changes in the microbial diversity also leading to a chronic inflammatory status, as recently shown by Barbara et al68 All these changes threaten the microbiota diversity and allow pathogenic bacteria that contribute to postsurgical complications to thrive.…”
Section: Influence On and Changes In The Gut Microbiota After Intestimentioning
confidence: 99%